Dampak Qira'at terhadap Penafsiran: Analisis Farsy al-Huruf dalam Tafsir Marah Labid Surah Al-Baqarah: An Analytical Study of Farsh al-Hurūf in Tafsir Marāh Labīd of Surah Al-Baqarah - Feni Tamimul Ummah; Tri Tami Gunarti; Mubarok Ahmadi (AL ITQAN: Jurnal Studi Al-Qur'an, 2024)
The study of Qur'anic interpretation is not only limited to classical aspects such as asbabun nuzul (circumstances of revelation), Makki-Madani classification, and the coherence (munasabah) of verses but also includes the influence of qira’at variations in understanding Qur'anic words. Qira’at, as a discipline within ulumul Qur’an (the sciences of the Qur'an), has become an essential tool in Qur'anic exegesis. This study aims to examine whether qira’at influences the interpretation in Tafsir Marāh Labīd, particularly in the exegesis of Surah Al-Baqarah. Using a qualitative approach with textual analysis methods, this research analyzes several verses in Surah Al-Baqarah that exhibit differences in recitation due to qira’at variations. The formal object of this research is the analytical approach to Qirā’āt, particularly farsh al-ḥurūf, in the interpretation of the Qur’an, while the material object is Surah Al-Baqarah. The findings indicate that the qira’at presented by Shaykh Nawawi in his interpretation of Surah Al-Baqarah has an impact on meaning production and exegesis. At least ten instances of Farsh al-Hurūf in Surah Al-Baqarah affect interpretation. These variations have different implications, including: Substantial impact, which explains differences among Islamic jurisprudential (fiqh) schools of thought. Editorial impact, which influences the distinction in meaning between khitab (speech) and mukhattab (the addressee). Non-substantial meaning differences, which explore synonyms of specific words. Although not all of Shaykh Nawawi’s discussions on qira’at result in substantial changes in meaning production, they significantly influence the editorial aspects of interpretation.